1987
DOI: 10.1152/ajpheart.1987.252.3.h566
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a pathogenetic role of xanthine oxidase in the "stunned" myocardium

Abstract: Recent evidence suggests that postischemic myocardial dysfunction (or myocardial "stunning") may be mediated by oxygen free radicals, but the mechanism for their production remains unknown. To explore the role of xanthine oxidase as a potential source of free radicals, open-chest dogs undergoing a 15-min occlusion of the left anterior descending coronary artery (LAD) followed by 4 h of reperfusion (REP) received intravenously either allopurinol (50 mg/kg 48 h, 20 h, and 30 min before occlusion, 10 mg/kg 1 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…20 In humans, studies report myocardial XO activity to be either high, 21 low, 22 or undetectable. 23,24 Although there is some considerable evidence that suggests that the enzyme XO may indeed be expressed in the human myocardium, [25][26][27] we believe that the effect may be local. No systemic effects from the myocardial activity of XO have been reported.…”
Section: Discussionmentioning
confidence: 89%
“…20 In humans, studies report myocardial XO activity to be either high, 21 low, 22 or undetectable. 23,24 Although there is some considerable evidence that suggests that the enzyme XO may indeed be expressed in the human myocardium, [25][26][27] we believe that the effect may be local. No systemic effects from the myocardial activity of XO have been reported.…”
Section: Discussionmentioning
confidence: 89%
“…The source of the oxygen radicals is unclear, although xanthine oxidase may be an important mediator of oxyradical production (21). Oxyradicals may interact with cellular proteins, lipids, calcium, and myofilaments to induce contractile depression.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the xanthine oxidase inhibitor, allopurinol, produced a marked improvement in the functional recovery of the stunned myocardium.136 Furthermore, allopurinol inhibited the increased cardiac production of urate observed in control dogs during ischemia and early reperfusion, indicating effective inhibition of xanthine oxidoreductase. 136 Attenuation of stunning has also been demonstrated with oxypurinol after 15137 and 90 minutes138 of ischemia and reperfusion. These data suggest that xanthine oxidase is one of the sources of the oxygen radicals that contribute to postischemic dysfunction in the dog.…”
Section: Decreased Sensitivity Of Myofilaments To Calciummentioning
confidence: 97%